Morphology dependent voltage sensitivity of gold nanostructures - Huang, Yu (2010)
In this thesis, the sensitivity of a range of plasmonic gold nanostructures to changes in ambient electric potential has been studied using a high quality objective-type dark-field imaging spectrometer, which was capable of measuring the signal from single nanoparticles. Optical response of the nanostructure to the change of physiologically relevant potential has been investigated experimentally and theoretically. Simulations to predict the sensitivity to potential changes were in good qualitative agreement with experimental data. The similar transients of scattering produced by potential cyclic voltammetry and potential step for gold film and gold nanoprism indicated that the mechanism of potential perturbation on the gold nanostructures was independent of their morphologies. The relationship between the morphologies of the gold nanostructure and their ability for voltage sensing had been investigated in detail. The cost-effective ultrathin gold film provides the highest voltage sensitivity and appears to be extremely promising as the basis for the design of an ultrasensitive plasmonic nanostructure sensor for electrical signals.